Sira Culture, Hadith and the Veneration of Muḥammad in the Later Middle Period: Ibn Nāṣir al-Dīn al-Dimašqī (d. 842/1438) as a Case Study - Bori, Caterina (Arabica, 2023)
Overall, the article argues that the intended meaning and use of a text as rich as Ǧāmiʿ al-āṯār can be fully grasped only when we put it in close conversation with the Hadith culture and veneration for the Prophet of the time. It suggests the existence of a pervasive “Sira culture” binding people in a relationship of meaning to their shared memories of the life of the Prophet. Such culture was nurtured by remembrance of the Prophet’s excellency and life milestones. It aimed at cultivating salvific feelings of love for the Prophet that would assure believers a secure place in the Afterlife.